JOB STRESS AMONG PHYSICAL EDUCATION TEACHERS IN SENIOR SECONDARY SCHOOLS OF HIMACHAL PRADESH - Sharma, Seema; Lal, Rajender (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Himachal Pradesh, with its diverse topography and climatic zones, presents a distinct environment for physical education teachers employed in senior secondary schools. The present study investigates the extent and nature of job-related stress among 200 randomly selected physical education teachers (110 males and 90 females) from various government and private institutions across the state. Utilizing the Occupational Stress Index (OSI) developed by Srivastava and Singh (1984), the research examines differences in stress levels based on gender, school location (urban/rural), and type of institution (government/private). The findings indicate that female teachers generally experience higher job stress than their male counterparts, particularly in government schools, while male teachers in private schools report greater stress than female teachers in the same sector. The results highlight the need for targeted interventions to address occupational stress in this professional group.